Biological oceanographic processes - Parsons, Timothy R.; Takahashi, Masayuki; Hargrave, Barry (Oxford, England Pergamon Press, 1984)
Pergamon international library of science, technology, engineering, and social studies series
Keywords: Primary productivity (Biology); Marine plankton; Marine ecology